Efeitos anarmônicos e transições de fase em Pb1¡xLaxTiO3: estudo por espalhamento Raman dos efeitos de substituição catiônica, temperatura e pressão hidrostática - Joya, Miryam Rincón (Universidade Federal de São Carlos, 2008)
In this work were studied e®ects of cationic substitution, hydrostatic pressure and temperature on the phonon spectra of PLT samples, Pb1¡xLaxTiO3 (PLT), using Raman scattering technique. The samples having La concentration x= 0, 2.5, 5, 10, 15 and 20%, were prepared by the classic powder mixture of oxides. Other complementary techniques were used to characterize the samples as X-ray Di®raction, Scanning Electronic Microscopy (SEM), apparent density measurements (ADM). Besides these cited experimental techniques, the Classic Molecular Dynamic Simulation was used to simulate, theoretically, the Raman scattering experimental results in PLT samples. The vibrational transverse optical (TO) mode frequency, with the lowest value, was specially explored in order to characterize and study the tetragonal-ferroelectric to cubic-paraelectric phase transition observed in PLT samples. With this set of results was possible to create a three-dimensional diagram for the structural phase transition as a function of La concentration, temperature and hydrostatic pressure. In this diagram is seen the critical values for pressure (Pc), La concentration (xc) and temperature (Tc) at the phase transition for each sample. Besides the phase diagram, the results also permitted to determine coe±cients for temperature, pressure and vibrational modes of materials. For the theoretical MD simulation of the structural phase transition induced by temperature was proposed a total potential function for four atoms, determining the ion-ion interaction on the crystalline structure based on the three atoms potential used to simulate PbTiO3. These simulated results show that this potential model can describe correctly the general structural behavior of PLT samples. These findings are in good agreement with the experimental results.
Keywords: Cerâmicas ferroelétricas; Transição de fase; Temperatura; Pressão hidrostática; Diagrama de fase tridimensional; CIENCIAS EXATAS E DA TERRA::FISICA